2010
DOI: 10.1016/j.jacc.2009.07.078
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Nature of Coronary Artery Lesion Morphology Assessed by Serial Virtual Histology Intravascular Ultrasound Tissue Characterization

Abstract: Most VH-TCFAs healed during 12-month follow-up, whereas new VH-TCFAs also developed. PITs, VH-TCFAs, and ThCFAs showed significant plaque progression compared with fibrous and fibrocalcific plaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
2
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(182 citation statements)
references
References 26 publications
9
161
2
10
Order By: Relevance
“…The finding may partially support the concept why larger non-calcified plaque volumes were associated with future cardiac events in the aforementioned study [28]. In the intravenous ultrasound (IVUS) study examining the dynamic nature of coronary atherosclerosis, all non-calcified plaque components by IVUS such as pathological intimal thickening (PIT), virtual histology IVUS derived thin-capped fibroatheroma (VH-TCFA), thick-capped fibroatheroma (ThCFA) and fibrotic plaque could convert to other type of non-calcified components [41]. Also, PIT, VH-TCFA and ThCFA are likely to increase in volume overtime compared to more pathologically stable plaque such as fibrotic and fibro-calcified plaques.…”
Section: Discussionmentioning
confidence: 99%
“…The finding may partially support the concept why larger non-calcified plaque volumes were associated with future cardiac events in the aforementioned study [28]. In the intravenous ultrasound (IVUS) study examining the dynamic nature of coronary atherosclerosis, all non-calcified plaque components by IVUS such as pathological intimal thickening (PIT), virtual histology IVUS derived thin-capped fibroatheroma (VH-TCFA), thick-capped fibroatheroma (ThCFA) and fibrotic plaque could convert to other type of non-calcified components [41]. Also, PIT, VH-TCFA and ThCFA are likely to increase in volume overtime compared to more pathologically stable plaque such as fibrotic and fibro-calcified plaques.…”
Section: Discussionmentioning
confidence: 99%
“…5) Several subsequent studies then evaluated the incidence, distribution, and clinical outcomes of VH-TCFA. [16][17][18] However, only a few studies evaluated the diagnostic accuracy of VH-IVUS to identify TCFA. Sawada, et al assessed 126 coronary lesions (culprit and nonculprit lesions) by VH-IVUS and OCT in 56 patients with angina including acute coronary syndrome and demonstrated that the positive ratio of VH-IVUS for detecting definite TCFA, which was defined as a plaque meeting the TCFA criteria in both methods, was 45.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several other researchers have used combined intravascular imaging to study coronary atheroma and changed our understanding about plaque evolution. Diletti et al used serial combined IVUS-VH-OCT imaging to study plaque characteristics in bifurcation lesions and found no difference in the fibrous cap thickness and necrotic core component at 6 months followup concluding that plaque evolution is a slow process and contradicted the findings of a previous report that used serial stand-alone IVUS to assess changes in plaque morphology at 1-year follow-up [25,66]. In another report, combined IVUS-OCT imaging was used to assess plaques that ruptured and caused events, plaques that had a silent rupture and nonruptured TCFAs.…”
Section: Multimodality Imagingmentioning
confidence: 89%
“…Preliminary IVUS studies showed that vulnerable plaques have focal manifestations and are mainly located proximally within the coronary arteries and at coronary bifurcations [17][18][19]. IVUS also enabled assessment of the effect of systemic and local factors on the progression of atherosclerosis [20][21][22][23][24], allowed morphologic comparison of symptomatic versus asymptomatic plaque rupture, serial assessment of plaque evolution [25], and the effect of different treatments on this process [26][27][28].…”
Section: Intravascular Ultrasoundmentioning
confidence: 99%